Gut microbiota-astrocyte axis: new insights into age-related cognitive decline - Zhang, Lan; Wei, Jingge; Liu, Xilei; Li, Dai; Pang, Xiaoqi; Chen, Fanglian; Cao, Hailong; Lei, Ping (Neural regeneration research, 2025)
With the rapidly aging human population, age-related cognitive decline and dementia are becoming increasingly prevalent worldwide. Aging is considered the main risk factor for cognitive decline and acts through alterations in the composition of the gut microbiota, microbial metabolites, and the functions of astrocytes. The microbiota-gut-brain axis has been the focus of multiple studies and is closely associated with cognitive function. This article provides a comprehensive review of the specific changes that occur in the composition of the gut microbiota and microbial metabolites in older individuals and discusses how the aging of astrocytes and reactive astrocytosis are closely related to age-related cognitive decline and neurodegenerative diseases. This article also summarizes the gut microbiota components that affect astrocyte function, mainly through the vagus nerve, immune responses, circadian rhythms, and microbial metabolites. Finally, this article summarizes the mechanism by which the gut microbiota-astrocyte axis plays a role in Alzheimer's and Parkinson's diseases. Our findings have revealed the critical role of the microbiota-astrocyte axis in age-related cognitive decline, aiding in a deeper understanding of potential gut microbiome-based adjuvant therapy strategies for this condition.